أثر تطبيقات إدارة المعرفة والتعلم التنظيمي في الأداء الاستراتيجي في مؤسسات القطاع العام في سلطنة عمان من وجهة نظر الإداريين - طويرشي، سعيد خليفة علي
This study explored to identify the extent of the impact of knowledge management applications and organizational learning on the strategic performance of public sector in Sultanate of Oman, according to the views of its employees, and to answer the study’s questions, the researcher used the descriptive survey approach, and the questionnaire was used as a tool to collect the data. The sample to which the study was applied included (362) employees at the Ministry of Labor during the year 2020, and the researcher used a number of statistical methods through the Statistical Package Program (SPSS), and the results showed that there is a high impact of knowledge management applications in all its basic processes (knowledge generation, knowledge storage) Spreading knowledge, application of knowledge ) at the level of learning, growth and the level of operations in the public sector in Sultanate of Oman from the point of view of its employees, rejecting the first and second hypotheses, while also concluded that there is a high impact of organizational learning in its dimensions (the strategic dimension, the cultural dimension, the organizational dimension) at the level of learning and growth, the level of operations and the level of customers in the public sector in Sultanate of Oman from the viewpoint of their employees. The study came out with a number of recommendations, including: That the Ministry of Labor begin to lay down the appropriate strategy to implement knowledge management and organizational learning in line with its policy, and the general policy of the Oman Strategy 2040. In addition, to paying attention to knowledge management by the ministry to achieve quality in all services provided to beneficiaries, and to establish a special section for knowledge management. The study also recommended interest in adopting a flexible organizational structure that encourages the opening of communication channels between different functional levels to exchange creative ideas.